The Domestic and the Oriental in the Material Cultural Heritage of Bosnian-Herzegovinian Muslims - Čelić, Džemal (Prilozi za orijentalnu filologiju, 2017)
After the acceptance of Islam, Bosnians and Herzegovinians did not break their earlier cultural and civilizational streams off. On the contrary, long lasti ng symbiosis started between the existing, autochtonous culture and Oriental- -Islamic influences. That symbiosis was visible in the intellectual and even more in the material sphere of cultural heritage of Bosnian and Herzegovinian Muslims. Medieval art of old Bosnian pre-Islamic tombstones (stećak) continued to exist in Islamic nishan-tombstones which could be found in more than hundred sites. Epitaphs on that tombstones were vvritten in vernacular called “Bosnian language” (bosančica). Oriental-Islamic form of bashlik-tombstones, with Arabic-Islamic epigraphy, started to prevail during and after the 16th century, but the difference betvveen tombstones stili existed in some regions. Regional differences were especially visible in architecture, with three basic regional characteristics prevailing: Medieval-Bosnian, Sarajevo-Foča region and Herzegovinian, as well as with lot of transitional areas and appearances. After the acceptance of Islam, Bosnians and Herzegovinians did not break their earlier cultural and civilizational streams off. On the contrary, long lasti ng symbiosis started between the existing, autochtonous culture and Oriental- -Islamic influences. That symbiosis was visible in the intellectual and even more in the material sphere of cultural heritage of Bosnian and Herzegovinian Muslims. Medieval art of old Bosnian pre-Islamic tombstones (stećak) continued to exist in Islamic nishan-tombstones which could be found in more than hundred sites. Epitaphs on that tombstones were vvritten in vernacular called “Bosnian language” (bosančica). Oriental-Islamic form of bashlik-tombstones, with Arabic-Islamic epigraphy, started to prevail during and after the 16th century, but the difference betvveen tombstones stili existed in some regions. Regional differences were especially visible in architecture, with three basic regional characteristics prevailing: Medieval-Bosnian, Sarajevo-Foča region and Herzegovinian, as well as with lot of transitional areas and appearances.